2011
DOI: 10.1007/s10482-011-9656-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic study of the species within the family Streptomycetaceae

Abstract: Species of the genus Streptomyces, which constitute the vast majority of taxa within the family Streptomycetaceae, are a predominant component of the microbial population in soils throughout the world and have been the subject of extensive isolation and screening efforts over the years because they are a major source of commercially and medically important secondary metabolites. Taxonomic characterization of Streptomyces strains has been a challenge due to the large number of described species, greater than an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
186
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(204 citation statements)
references
References 56 publications
7
186
0
5
Order By: Relevance
“…The DNA-DNA reassociation values were 41.5¡0.7 % and 12.1¡1.1 %, respectively, which were below the threshold value of 70 % recommended by Wayne et al (1987) for assigning strains to the same species. Labeda et al (2012) considered that a combination of 16S rRNA gene sequence and phenotypic data, notably standard cultural and morphological properties, provided a reliable means of assigning novel species to the genus Streptomyces. Therefore, a comparative study, which revealed that strain NEAU-G9 T differed from its closest relative S. yanglinensis JCM 13275 T and phylogenetically closest neighbour S. misakiensis JCM 4062 T in morphological, physiological and biochemical characteristics, was performed.…”
Section: Streptomyces Cocklensis Bk168 T (Fr692107)mentioning
confidence: 99%
“…The DNA-DNA reassociation values were 41.5¡0.7 % and 12.1¡1.1 %, respectively, which were below the threshold value of 70 % recommended by Wayne et al (1987) for assigning strains to the same species. Labeda et al (2012) considered that a combination of 16S rRNA gene sequence and phenotypic data, notably standard cultural and morphological properties, provided a reliable means of assigning novel species to the genus Streptomyces. Therefore, a comparative study, which revealed that strain NEAU-G9 T differed from its closest relative S. yanglinensis JCM 13275 T and phylogenetically closest neighbour S. misakiensis JCM 4062 T in morphological, physiological and biochemical characteristics, was performed.…”
Section: Streptomyces Cocklensis Bk168 T (Fr692107)mentioning
confidence: 99%
“…They form an integral part of soil microbial communities and making up approximately 10% of total soil microbial flora (8). The majority of research focused on the classification of these saprophytic strains (9,10), albeit the genus contains few human and plant pathogens (4,11). Streptomyces species are causal agents of diseases in man (S. somaliensis and S. sudanesnsis); animals (Streptomyces species) and plants (Streptomyces scabies) (6,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Streptomyces consisting of Gram-positive filamentous bacteria belongs to the class Actinobacteria. Members of the genus Streptomyces have a wide range of metabolic abilities and produce numerous enzymes and chemical compounds, including antibiotics, enzyme inhibitors, vitamins, antitumour agents and antifungal compounds (Goodfellow & Fiedler, 2010;Labeda et al, 2012). Many studies have focused on Streptomyces, which is the largest genus in the domain Bacteria, and at the time of writing, contains more than 690 species and subspecies with validly published names (Munoz et al, 2011;Parte, 2014;Quast et al, 2013).…”
mentioning
confidence: 99%